Challenges in Evaluating the Cost-effectiveness of New Diagnostic Tests for HIV-Associated Tuberculosis - Andrews, Jason R. (Oxford University Press, 2013)
With an emerging array of rapid diagnostic tests for tuberculosis, cost-effectiveness analyses are needed to inform scale-up in various populations and settings. Human immunodeficiency virus (HIV)–associated tuberculosis poses unique challenges in estimating and interpreting the cost-effectiveness of novel diagnostic tools. First, gains in sensitivity and specificity do not directly correlate with impact on clinical outcomes. Second, the cost-effectiveness of implementing tuberculosis diagnostics in HIV-infected populations is heavily influenced by downstream costs of HIV care. As a result, tuberculosis diagnostics may appear less cost-effective in this population than among HIV-uninfected individuals, raising important ethical and policy questions about the design and interpretation of cost-effectiveness analyses in this setting. Third, conventional cost-effectiveness benchmarks may be inadequate for making decisions about whether to adopt new diagnostics. If we are to appropriately deploy novel diagnostics for tuberculosis to people living with HIV in resource-constrained settings, these challenges in measuring cost-effectiveness must be more widely recognized and addressed.